Introductory petition in the short process - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2019)
Introductory petition in the short process Every marriage process going to declare the nullity, regardless of its form, starts from introductory petition. A judge cannot examine any case until the petition is put forward by the one who can challenge the validity of marriage. Spouses and a promotor of justice have an unchangeable right to challenge the validity of marriage in some circumstances. This article is an attempt to define and determine the circumstances in which the parties can file for a shortened process, or the so called bishop process.